1984
DOI: 10.2355/isijinternational1966.24.950
|View full text |Cite
|
Sign up to set email alerts
|

Mold powder technology for continuous casting of aluminum-killed steel.

Abstract: Synopsis Mold powder technology for continuous casting of aluminum-killed steel was developed to produce the clean and crack free steel slabs. The following items were investigated: 1) Mass balance of A120~ in the molten powder pool. 2) A1203 absorption capacity o f the molten powder. 3) Uniformization of heat removal through the mold during continuous casting. 4) Change in powder viscosity with absorption of A1203. 5) Design of optimum powder viscosity by consideration of A1203 absorption during continuous ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
8
0
Order By: Relevance
“…Viscosity is one of the most important indexes for evaluating the performance of mold fluxes, as it has a significant effect on the lubrication of casting blanks. In industrial production, the viscosity of mold fluxes at 1300 • C (η) and casting speed (υ) generally meet the correlation η•υ = 1.0-3.5 (Poise m•min −1 ), so as to meet the demands for adequate lubrication and heat transfer [16]. A significant amount of research regarding the effect of Al 2 O 3 on the viscosity of different slag systems has been conducted [17][18][19][20][21][22], while little research has been reported on mold fluxes in the absence of SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Viscosity is one of the most important indexes for evaluating the performance of mold fluxes, as it has a significant effect on the lubrication of casting blanks. In industrial production, the viscosity of mold fluxes at 1300 • C (η) and casting speed (υ) generally meet the correlation η•υ = 1.0-3.5 (Poise m•min −1 ), so as to meet the demands for adequate lubrication and heat transfer [16]. A significant amount of research regarding the effect of Al 2 O 3 on the viscosity of different slag systems has been conducted [17][18][19][20][21][22], while little research has been reported on mold fluxes in the absence of SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It can be stated as either the V‐ratio (%CaO/%SiO 2 ) or a more complex term like Bi. It was reported that the alumina absorption rate (g cm −2 s −1 ) correlates well with the basicity index Bi10, 11 according to the following expression: …”
Section: Laboratory Testsmentioning
confidence: 99%
“…For the mould powders F‐bearing and F‐free, the alumina absorption rate is expected to be similar because they have similar Bi10, 11; see Table 1.…”
Section: Industrial Testsmentioning
confidence: 99%
“…Use of Uniformly Flowing Powders35- 39) Needless to say, proper selection of a casting powder in accordance with other specific casting conditions for the steel is imperative. Here, the properties required of such a powder are the lubricity between mold and solidified shell, thermal insulation and oxidation prevention of the molten steel, removal by absorption of floating alumina particles, and many others.…”
Section: Technologies For Preventing Surface Longitudinal Cracksmentioning
confidence: 99%